Effects of climate variability on growth and establishment patterns of Nothofagus macrocarpa in central Chile - Venegas-González, Alejandro; Roig Juñent, Fidel; Gutiérrez, Alvaro G; Peña-Rojas, Karen; Tomazello Filho, Mario (BOSQUE, 2018)
An increase in drought conditions over the last century has been documented in Central Chile, a fact that could affect the Mediterranean forests, especially the northernmost Nothofagus populations from South America (Nothofagus macrocarpa). For this reason, it is key to study the climate influence on radial growth and trees establishment to design strategies of conservation and mitigation in the face of a climate change situation. In this study, 10 trees populations of N. macrocarpa were selected across natural distribution for a dendroecological analysis. The relationship between droughts and radial growth was analyzed annually, while the influence of water favorable conditions in trees establishment was evaluated in periods of 10 years. Results identified three growth patterns: (i) most degraded populations of the Coastal Mountains (young trees predominate), (ii) low-intervened forests found at a higher altitude in the Coastal Mountains and (iii) low-intervened forests of the Andes Mountains. All populations showed positive correlations with the SPEI-drought index during winter-spring, being sensitive up to 36 months after a dry period. More than 64% of the years with lowest growth are associated with historical droughts in all the chronologies, whereas trees establishment linked to humid periods was found especially in the less degraded forests (37-41% trees). These results provide an ecological vision of the climatic sensitivity of the Chilean Mediterranean forest and can contribute to the design restoration, conservation and mitigation actions in situations of global warming.